Genetic and functional identification of the likely causative variant for cholesterol gallstone disease at the ABCG5/8 lithogenic locus1. Issue 6 (25th January 2013) - von Kampen, Oliver; Buch, Stephan; Nothnagel, Michael; Azocar, Lorena; Molina, Hector; Brosch, Mario; Erhart, Wiebke; von Schönfels, Witigo; Egberts, Jan; Seeger, Marcus; Arlt, Alexander; Balschun, Tobias; et al.
Abstract The sterolin locus (ABCG5/ABCG8) confers susceptibility for cholesterol gallstone disease in humans. Both the responsible variant and the molecular mechanism causing an increased incidence of gallstones in these patients have as yet not been identified. Genetic mapping utilized patient samples from Germany (2, 808 cases, 2, 089 controls), Chile (680 cases, 442 controls), Denmark (366 cases, 766 controls), India (247 cases, 224 controls), and China (280 cases, 244 controls). Analysis of allelic imbalance in complementary DNA (cDNA) samples from human liver (n = 22) was performed using pyrosequencing. Transiently transfected HEK293 cells were used for [3H]‐cholesterol export assays, analysis of protein expression, and localization of allelic constructs. Through fine mapping in German and Chilean samples, an ∼250 kB disease‐associated interval could be defined for this locus. Lack of allelic imbalance or allelic splicing of the ABCG5 and ABCG8 transcripts in human liver limited the search to coding single nucleotide polymorphisms. Subsequent mutation detection and genotyping yielded two disease‐associated variants: ABCG5‐R50C (P = 4.94 × 10−9) and ABCG8‐D19H (P = 1.74 × 10−10) in high pairwise linkage disequilibrium (r2 = 0.95). [3H]‐cholesterol export assays of allelic constructs harboring these genetic candidate variants demonstrated increased transport activity (3.2‐fold, P = 0.003) only for the ABCG8‐19H variant, which was also superior in nested logistic regression models in German (P = 0.018), Chilean (P = 0.030), and Chinese (P = 0.040) patient samples. Conclusion: This variant thus provides a molecular basis for biliary cholesterol hypersecretion as the mechanism for cholesterol gallstone formation, thereby drawing a link between "postgenomic" and "pregenomic" pathophysiological knowledge about this common complex disorder. (HEPATOLOGY 2012)